PIDANA MATI DAN HAK ASASI MANUSIA - Nikson Gans Lalu (Fakultas Hukum Universitas Kristen Indonesia, 2015)
Death penalty is regulated in positive law of Indonesia, both governed in Civil Code and outside Code of Criminal Law, such in the Terrorism Law, Narcotics Law, and Corruption Crime Act Eradication Law. This indicates that death penalty is viewed as relevant in line with the crime dynamics growing in the community. Debates regarding death penalty among the pros and cons still take place in Indonesia so it raises a question among the people, how the existence of death penalty is seen of the viewpoints of Pancasila and Human Rights? Indeed, Pancasila contains balance value between one principle to another. If the Pancasila is seen partialy, then the answer arises on the question is the death penalty is contradictory to the Pancasila and Human Rights, however some answer also indicate it is not contracdictory to the Pancasila and Human Rights. National Draft Code of Criminal Law consistently retains the death penalty. However, in itâ€Ÿs formulation policy remains considering the individual protection, namely enactment on provisions regarding â€œthe suspension of death penalty executionâ€ or â€œconditional death penalty, â€œif in the probation period (10 years) the convicted criminal does not show a good conduct, then the death penalty may be changed to life time imprisonment or 20 years imprisonment. The basic idea of maintaining the death penalty is to avoid peopleâ€Ÿs demand/reaction which is revenge in nature or â€œextralegal executionâ€ in nature. Kata Kunci: Pidana mati